A simple capillary column GC method for analysis of palm oil-based polyol esters - Yunus, Robiah; Lye, Ooi Tian; Fakhru'l-Razi, A.; Basri, Shahnor (American Oil Chemists' Society, 2002)
A reliable, simultaneous analysis of palm oil polyol esters using capillary column GC is described. The polyol esters were esterified from palm oil methyl esters (POME) and palm kernel oil methyl esters (PKOME) with trimethylolpropane [2-ethyl-2-(hydroxymethyl)-1,3-propanediol; TMP] to produce the biodegradable base oil for lubricant production. Analysis was performed using a high-temperature capillary column, SGE HT5 operated at a temperature gradient of 6°C/min starting from 80 to 340°C. Before injection, the sample was derivatized with N,Obis(trimethylsilyl)trifluoroacetamide in ethyl acetate ar 40°C for at least 10 min. This procedure provides a complete separation of reaction products: TMP, methyl esters, monoesters (ME), diesters (DE), and triesters (IE). As expected, the ME from palm kernel oil was resolved into five major peaks, DE into seven peaks, and TE into 10 peaks. Since no standard was available for this sample, the identities of the peaks were established by a secondary standard that was derived from pure methyl esters. This GC method has made possible the simultaneous determination of reaction product compositions in order to assess the extent of reaction.